Pengelolaan Alokasi Anggaran Kelurahan (Aak) Untuk Pemberdayaan Masyarakat Di Kelurahan Makarti Jaya Kecamatan Makarti Jaya Kabupaten Banyuasin - Karwanto, Karwanto; Lionardo, Andries; Intan, Lies Nur (Journal of Law & Policy Review, 2024)
This article or writing aims to describe the management of sub-district budget allocations (AAK) for community empowerment as well as community involvement in managing sub-district budget allocations (AAK) for community empowerment in Makarti Jaya Village, Makarti Jaya District, Banyuasin Regency. Data was collected through in-depth interviews and analysis of documents such as work plans, musrembang reports, and budget records and analyzed qualitatively. From the research results, the management of budget allocations in Makarti Jaya Subdistrict for community empowerment is still not optimal. Despite progress in planning, organizing, implementing, and monitoring, there are challenges such as budget constraints, implementation of training, and lack of systematic evaluation. Community engagement is critical to program success, but budget constraints and post-training support hamper results. Minimal oversight also reduces transparency. To increase effectiveness, there needs to be improvements in planning, implementation and supervision, as well as increased community support and participation.